Penerapan Media Permainan Balok Angka Terhadap Kemampuan Berhitung Anak Usia 5-6 Tahun Di TK Baitul Izzah Kota Bengkulu - Putri Heriyani Nabila, Dea; Wulandari, Femi; Novita Sandra Putri, Vina; Anisya Putri, Welis (UIN Fatmawati Sukarno Bengkulu, 2025)
This study discusses the application of the Number Block Game in introducing numbers to children aged 5-6 years at Baitul Izzah Kindergarten, Bengkulu City. Disclosing accurate data in the application of number block media games to introduce numbers to children aged 5-6 years at Baitul Izzah Kindergarten, Bengkulu City, the author uses qualitative methods by collecting data through primary data and secondary data. The results of the study can be described that the application of number block media games to introduce numbers to children aged 5-6 years at Baitul Izzah Kindergarten, Bengkulu City can introduce various forms of blocks to children, motivate children to make something from number blocks, develop children's creativity according to their imagination, develop children's cognitive abilities in thinking, especially early counting, namely recognizing the concept of numbers easily, There is an increase in counting ability after the application of number block media games in children aged 5-6 years at Baitul Izzah Kindergarten, Bengkulu City. The increase in counting ability occurs because the application of number block media games in children increases children's logical and systematic thinking patterns, trains courage in answering every question asked and also when this game is applied the child is more concentrated and the child is very quick to respond and answer the numbers listed in the number block media game.